Does service quality of self-checkout technology improve purchasing intention in Malaysia retail industry? - Wen Siah, Jia; Fen Fam, Soo (International Journal of Engineering and Technology, 2018)
The aim of this research is to determine the factors that affect self-checkout technology service quality and to investigate the relationships among service quality, customer satisfaction and purchasing intention in Malaysian supermarkets. The service quality dimensions include speed, ease of use, reliability, enjoyment and control was adapted from Dabholkarâ€™s attribute based model. A questionnaire-based survey was used and data were collected from 394 customers from selected supermarket at Putrajaya. The data were analyzed using multiple regression analysis by IBM-SPSS version 23. All hypothesis formulated in the study were positive significant. The contribution of this study is to provide practical insights into service quality dimensions for managing customer satisfaction and business performance.Â